PENINGKATAN KEMAMPUAN MENULIS SISWA MELALUI MENGGUNAKAN METODE MENULIS BERANTAI (ESTAFET WRITING) - Fadlilah, Husni Nur; Endang, Ujang; Yuniartin, Titin (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2019)
This research is motivated by the students' learning outcomes of writing which are still low, in addition to the role of teachers who still dominate learning using inappropriate and conventional methods causing students to become bored in the learning process at MI PUI Kaum Banjarsari-Ciamis, especially in Indonesian subjects . Writing ability is highly considered in MI PUI Kaum, so MI PUI Kaum sets the Minimum Mastery Criteria (KKM) for learning Indonesian Language is 75. However, the situation that occurs in the field level of students' writing ability in Indonesian subjects especially in Poetry material is still below the KKM ie with an average of 71.64 out of 17 students. The research method used was the Classroom Action Research (PTK) method of Kurt Lewin's model in class V students A. Data collection techniques used in this study were observation techniques, interview techniques, test techniques, descriptive assessment and techniques. Based on the results of the study it can be concluded that: 1) Teachers have increased ability in preparing lesson plans using the relay writing method, cycle I 89.60, cycle II 90.53, and cycle III 91.83; 2) The teacher has increased the ability to carry out learning by using the relay writing method, cycle I 89.16, cycle II 90.88, and cycle III 91.66; 3) The ability to write students using the method of chain writing (relay writing) has increased, namely pre cycle 71.64, cycle I 71.47, cycle II 75.29, and cycle III 79.41.